2011
DOI: 10.1038/ncomms1239
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation driven by tumour-specific Th1 cells protects against B-cell cancer

Abstract: The immune system can both promote and suppress cancer. Chronic inflammation and proinflammatory cytokines such as interleukin (IL)-1 and IL-6 are considered to be tumour promoting. In contrast, the exact nature of protective antitumour immunity remains obscure. Here, we quantify locally secreted cytokines during primary immune responses against myeloma and B-cell lymphoma in mice. Strikingly, successful cancer immunosurveillance mediated by tumour-specific CD4+ T cells is consistently associated with elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
252
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(262 citation statements)
references
References 59 publications
9
252
0
1
Order By: Relevance
“…In contrast, inflammation driven by a tumour-specific T-helper cell, type 1 (Th1) was consistently associated with elevated levels of proinflammatory cytokines and effective tumour surveillance against myeloma cells. Our results support the finding by Haabeth et al (2011) and indicate that genetically determined high IL1B expression is associated with higher risk of MM but, on the other hand, also with better survival following treatment. In conclusion, we found that genetically determined low IL1B expression is associated with lower risk of MM.…”
Section: Controlssupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, inflammation driven by a tumour-specific T-helper cell, type 1 (Th1) was consistently associated with elevated levels of proinflammatory cytokines and effective tumour surveillance against myeloma cells. Our results support the finding by Haabeth et al (2011) and indicate that genetically determined high IL1B expression is associated with higher risk of MM but, on the other hand, also with better survival following treatment. In conclusion, we found that genetically determined low IL1B expression is associated with lower risk of MM.…”
Section: Controlssupporting
confidence: 82%
“…The wild-type Callele of IL1B C-3737T and non-carriage of the haplotype TGT were associated with longer time-to-treatment failure and overall survival in myeloma patients treated with highdose treatment with haematopoietic stem cell support (Vangsted et al, 2011). The dualism of the cytokine response has been addressed in a recent publication (Haabeth et al, 2011); this in vivo study on mice showed that proinflammatory cytokines, such as IL6 and IL1B, could promote tumour development when involved in inflammation without tumour specificity (Haabeth et al, 2011). In contrast, inflammation driven by a tumour-specific T-helper cell, type 1 (Th1) was consistently associated with elevated levels of proinflammatory cytokines and effective tumour surveillance against myeloma cells.…”
Section: Controlsmentioning
confidence: 99%
“…These animal models have shown that cytokines derived from T H 1 cells such as interferon-gamma, interleukin-1, and TNF-alpha are important in stimulating tumor-associated macrophages. Conversely, T H 2 cell are associated with immunosuppression and are generally associated with inferior outcome and may contribute to immunosuppression in B-cells lymphomas [19,21]. It is known that pre-treatment circulating lymphocytes are skewed toward T H 2 and revert to a T H 1 phenotype with successful therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…1 T-cells as key in establishing an anti-tumor microenvironment [20]. T H 1 cells in particular stimulate and upregulate antigen presentation and tumor clearance [21]. Improved antigen presentation has been shown to be a key survival determinant in patients with DLBCL [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…170 In a recent study, Haabeth and colleagues reported that successful cancer immunosurveillance mediated by tumor-specific CD4(+) T cells is consistently associated with elevated local levels of both proinflammatory and T helper 1-associated cytokines, indicating that inflammation driven by T helper 1 cells may prevent B-cell lymphoma. 171 Besides, transgenic mice with obstruction of NFκB activation were very vulnerable both to a severe immune challenge and to a systemic bacterial infection.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%